microRNAs: innovative targets for cerebral ischemia and stroke - Ouyang, Yi-Bing (2013)
Stroke is one of the leading causes of death and disability worldwide. Because stroke is a multifactorial disease with a short therapeutic window many clinical stroke trials have failed and the only currently approved therapy is thrombolysis. MicroRNAs (miRNA) are endogenously expressed noncoding short single-stranded RNAs that play a role in the regulation of gene expression at the post-transcriptional level, via degradation or translational inhibition of their target mRNAs. The study of miRNAs is rapidly growing and recent studies have revealed a significant role of miRNAs in ischemic disease. miRNAs are especially important candidates for stroke therapeutics because of their ability to simultaneously regulate many target genes and since to date targeting single genes for therapeutic intervention has not yet succeeded in the clinic. Although there are already quite a few review articles about miRNA in ischemic heart disease, much less is currently known about miRNAs in cerebral ischemia. This review summarizes current knowledge about miRNAs and cerebral ischemia, focusing on the role of miRNAs in ischemia, both changes in expression and identification of potential targets, as well as the potential of miRNAs as biomarkers and therapeutic targets in cerebral ischemia.